Family matters: the interpretation of Lycian "Funerary Banquet" reliefs - Lockwood, S (2010)
A distinct Lycian culture flourished in southwestern Asia Minor from the late sixth to the late fourth century BC. The majority of extant evidence for this culture is archaeological, and is primarily restricted to sepulchral monuments. Often associated with Lycian tombs are relief sculptures, the interpretation of which is made particularly difficult by the lack of first person, primary sourcs. Nevertheless, these scenes are most often described as 'funerary banquets' by comparison with their contemporary Perso-Anatolian and Greek counterparts. The paper focuses on Lycian banquet reliefs dated to the late fifth and fourth centuries BC, the majority of which feature a reclining male figure accompanied by a seated female companion, most often in conjunction with subsidiary figures of differing sexes and ages. Absent from the majority of the Lycian scenes are the accoutrements of the banquet (tables, food, storage vessels), with the exception of the drinking cup usually held in the hand of the reclining male figure. The focus of the scene is therefore removed from the action of the 'banquet', and is placed on the figures themselves. The subsidiary figures, particularly the children who are often shown in intimate contact with the adults, thereby emphasize the familial quality of the scenes. This paper analyzes both the typical and the exceptional Lycian banquet scenes (notably those of the Nereid Monument), in the contemporary cultural context of Greece and Anatolia, concluding that the Lycian reliefs were meant to celebrate the bonds of family. Whether the family is depicted during life or in the afterlife cannot be discerned based on the available evidence, but the setting does not change the meaning of the reliefs.